ASSESSMENT OF OCCURRENCE AND DIVERSITY OF APPLE VIRUSES IN SOUTH KAZAKHSTAN - Kerimbek, N. M.; Kapytina, A. І.; Khusnitdinova, M. A.; Taskuzhina, A. K.; Gritsenko, D. A. (ЗКАТУ им. Жангир хана, 2024)
Apples (Malus spp.) are one of the popular fruits in the world. Apple cultivars face significant threats from various viruses and virus-like diseases. These include well-known ones such as Apple mosaic virus (ApMV), Apple necrotic mosaic virus (ApNMV), Apple stem pitting virus (ASPV), Apple stem grooving virus (ASGV), and Apple chlorotic leaf spot virus (ACLSV). These viruses are known to infect a wide range of apple cultivars, leading to various symptoms such as stem grooving, chlorotic leaf spots, stem pitting, and mosaic patterns on the fruits and leaves. The objective of this study was to assess the incidence of the five viruses in apple-growing regions of southern Kazakhstan. The average positive rates of ACLSV, ASPV and ASGV were 42.1%, 57% and 12.6% respectively. ApMV and ApNMV were not detected. The study revealed a high incidence of mixed infections of the three apple viruses in Kazakhstan, with 60.6% of the infected apple plants harboring more than one species of virus. The most frequent virus combination was ACLSV+ASPV, with an incidence of 31.7%, followed by ACLSV+ASGV (10.9%), ASPV+ASGV (10%) and ACLSV+ASPV+ASGV (8.2%). The high prevalence of single and mixed infections in surveyed regions underscores the need for comprehensive and integrated approaches to disease management such as multiplex RT-PCR. The assay allows for the simultaneous detection of multiple apple viruses in a single reaction, providing a rapid and efficient means of screening for multiple pathogens in apple plants.
Kerimbek, N. M. Аssessment of occurrence and diversity of apple viruses in south kazakhstan / N. M. Kerimbek, A. І. Kapytina, M. A. Khusnitdinova, A. K. Taskuzhina, D. A. Gritsenko. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - 2-2 (75). Ч. ІІ. - Р. 79-85.
Keywords: apple viruses; ApMV; ApNMV; ACLSV; ASPV; ASGV; RT-PCR; научный журнал; зкату